Use of nicotine replacement therapy and stop‐smoking medicines in a national sample of Aboriginal and Torres Strait Islander smokers and ex‐smokers. (1st June 2015) - Thomas, David P; Briggs, Viki L; Couzos, Sophia; Panaretto, Kathryn S; van der Sterren, Anke E; Stevens, Matthew; Borland, Ron
Abstract: Objective : To examine the use of nicotine replacement therapy (NRT) and the stop‐smoking medicines (SSMs) varenicline and bupropion in a national sample of Aboriginal and Torres Strait Islander smokers and recent ex‐smokers. Design, settings and participants: The Talking About The Smokes (TATS) project used a quota sampling design to recruit a nationally representative sample of 1721 smokers and ex‐smokers who had quit ≤ 12 months before from communities served by 34 Aboriginal community‐controlled health services and one community in the Torres Strait. Baseline surveys were conducted from April 2012 to October 2013. These were compared with 1017 daily smokers from the general Australian population surveyed by the International Tobacco Control Policy Evaluation Project (ITC Project) from July 2010 to May 2011. Main outcome measures: Past and intended use of NRT and SSMs, duration of use, and whether participants thought NRT and SSMs help smokers to quit. Results: Compared with other daily Australian smokers, lower proportions of Aboriginal and Torres Strait Islander daily smokers had ever used any NRT or SSMs (TATS, 37% v ITC, 58.5%) or used them in the past year (TATS, 23% v ITC, 42.1%). Nicotine patches were most commonly used by Aboriginal and Torres Strait Islander smokers and recent ex‐smokers (24%), followed by varenicline (11%) and nicotine gum (10%); most (74%) had got their last NRT at no cost. Among dependent Aboriginal and Torres Strait Islander daily smokers, those who were more socioeconomically advantaged were more likely than the disadvantaged to have used NRT or SSMs. Similar proportions of Aboriginal and Torres Strait Islander daily smokers and other Australian daily smokers said that NRT or SSMs help smokers to quit (TATS, 70% v ITC, 74.2%). Dependent Aboriginal and Torres Strait Islander smokers who had previously used NRT or SSMs were more likely to believe they help in quitting and to intend to use them in the future. Conclusion: Aboriginal and Torres Strait Islander daily smokers, particularly those who are most disadvantaged, are less likely to have used NRT or SSMs than other Australian daily smokers. Some of the barriers to use, including cost, are being overcome, but further improvements are possible.